2018
DOI: 10.1007/s11030-018-9834-3
|View full text |Cite
|
Sign up to set email alerts
|

New 7-piperazinylquinolones containing (benzo[d]imidazol-2-yl)methyl moiety as potent antibacterial agents

Abstract: A series of 7-piperazinylquinolones containing a (benzo[d]imidazol-2-yl)methyl moiety were designed and synthesized as new antibacterial agents. The antibacterial activity of title compounds was evaluated against Gram-positive (Staphylococcus aureus, Staphylococcus epidermidis and Bacillus subtilis) and Gram-negative (Escherichia coli, Pseudomonas aeruginosa and Klebsiella pneumonia) microorganisms. Among the tested compounds, the N1-cyclopropyl derivative 4a showed the highest activity against S. aureus, S. e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The synthesis of chiral amino alcohols‐benzimidazole hybrid starts with the reaction of monochloro acetic acid and 1,2‐diaminobenzene in 4 N HCl and then N ‐tosylation of 2‐(chloromethyl)‐1‐ H ‐benzimidazole 1 with p ‐toluensulfonyl chloride in pyridine gave 2‐(Chloromethyl)‐1‐[(4‐methylphenyl)sulfonyl]‐1 H ‐benzimidazole 2 . All spectroscopic and physical data of synthesized compound 1 and 2 are consistent with the literature . (Scheme ) The chiral amino alcohols‐benzimidazole hybrid compounds were synthesized the reaction of commercially available chiral amino alcohols with the 2‐(chloromethyl)‐ N ‐tosyl‐1‐ H ‐benzimidazole 2 .…”
Section: Resultssupporting
confidence: 63%
“…The synthesis of chiral amino alcohols‐benzimidazole hybrid starts with the reaction of monochloro acetic acid and 1,2‐diaminobenzene in 4 N HCl and then N ‐tosylation of 2‐(chloromethyl)‐1‐ H ‐benzimidazole 1 with p ‐toluensulfonyl chloride in pyridine gave 2‐(Chloromethyl)‐1‐[(4‐methylphenyl)sulfonyl]‐1 H ‐benzimidazole 2 . All spectroscopic and physical data of synthesized compound 1 and 2 are consistent with the literature . (Scheme ) The chiral amino alcohols‐benzimidazole hybrid compounds were synthesized the reaction of commercially available chiral amino alcohols with the 2‐(chloromethyl)‐ N ‐tosyl‐1‐ H ‐benzimidazole 2 .…”
Section: Resultssupporting
confidence: 63%
“…Compound 8 showed the highest activity ylococcus aureus, Staphylococcus epidermidis, Bacillus subtilis, and Escherichia co value of 0.097 μg/mL. Computational studies indicate the docking poses of against DNA gyrase, subunits A (PDB code: 2XCT) and subunit B (PDB cod comparable with the reference standard [73].…”
Section: To Overcome the Mdr Problem New Derivatives Of Gatifloxacin ...mentioning
confidence: 92%
“…[12][13][14] Developing new antibacterial agents by hybridizing two active scaffolds can lead to molecules having better inhibitory activities against the resistant bacteria. [15][16][17][18][19] Modifications of the core and substitutions are carried out on the piperazine moiety at C7 of the quinolone to develop inhibitors for resistant bacterial pathogens. In this prospect, Kulabas et al reported different aniline-linked ciprofloxacin as antibacterial and anti-mycobacterial agents, of which compound VI showed good inhibition against gram + ve and gram -ve bacteria with a MIC ranging from 1.25 to 4 μg/mL.…”
Section: Introductionmentioning
confidence: 99%
“…Diphenyl ethers like triclosan ( V ) and its derivatives are known to be potent antibacterial agents [12–14] . Developing new antibacterial agents by hybridizing two active scaffolds can lead to molecules having better inhibitory activities against the resistant bacteria [15–19] …”
Section: Introductionmentioning
confidence: 99%